In vitro evaluation of fungal endophytes of black pepper against Phytophthora capsici and Radopholus similis - Bhai, K Sreeja, M Anandaraj, R S (Journal of Spices and Aromatic Crops, 2016)
Experiment on in vitro screening of 125 endophytic fungi of black pepper against Phytophthora capsici indicated that 23 isolates showed more than 50% inhibition. The nematicidal activity of metabolites from endophytic fungi was also tested on Radopholus similis and the isolate BPEF73 (Daldinia eschscholtzii) showed highest mortality up to 60%. The isolates showing biocontrol potential were characterized based on internal transcribed spacer (ITS1 and ITS2) regions of rDNA. The sequence analysis of the isolates showed maximum identity with Annulohypoxylon nitens (BPEF25 and BPEF38), Daldinia eschscholtzii (BPEF41 and BPEF73), Fusarium spp. (BPEF72 and BPEF75), Ceriporia lacerata (BPEF81), Diaporthe sp. (BPEF11) and Phomopsis sp. (BPEF83). This is first report of endophytic association of above fungi in black pepper and the exploitation of their biocontrol potential against the major black pepper pathogens P. capsici and R. similis.